2001
DOI: 10.1590/s0101-81752001000400024
|View full text |Cite
|
Sign up to set email alerts
|

Brasacanthus sphoeroides gen. n., sp. n. (Acanthocephala, Echinorhynchidae) from a coastal marine fish of Paraná State, Brazil

Abstract: ABSTRACT. Brasacanlizus sphoeroides gen. n .. sp. n. is described from the marine fish, Sphoeroides greeleyi (Steindachner), taken in Paranagua Bay, Parana State, Brazil. The new genus differs from Acalilhocep/w/us Koelreuter, 177!. the nearest genus in the fami ly Echinorhynchidae, by having very flat and variable lemnisci in both sexes and a uterine egg reservoir in the female. The species is characterized by its spherical body form and in having parallel or diagonal testes. KEY WORDS. Acanthocephala, fish p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Three regular pairs of cement glands are typical of the many species of Acanthocephalus and Pseudoacanthocephalus , whereas the monotypic Pilum is characterized by four regular pairs ( Petrochenko 1956 , Williams 1976 ). Anuracanthorhynchus tritaxisentis Bursey, Vreibradic, Hatano & Rocha, 2006 and Brasacanthus sphoeroides Thatcher, 2001, the type-species and sole representatives of their respective genera, have their cement glands arranged in parallel, a pattern not found in Echinorhynchus (see Thatcher 2001 , Bursey et al 2006 ). The only species in the outgroup to display its six cement glands in the moniliform pattern is Frilloechinorhynchus meyeri (Gupta & Naqvi, 1986) (see Bhattacharya 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three regular pairs of cement glands are typical of the many species of Acanthocephalus and Pseudoacanthocephalus , whereas the monotypic Pilum is characterized by four regular pairs ( Petrochenko 1956 , Williams 1976 ). Anuracanthorhynchus tritaxisentis Bursey, Vreibradic, Hatano & Rocha, 2006 and Brasacanthus sphoeroides Thatcher, 2001, the type-species and sole representatives of their respective genera, have their cement glands arranged in parallel, a pattern not found in Echinorhynchus (see Thatcher 2001 , Bursey et al 2006 ). The only species in the outgroup to display its six cement glands in the moniliform pattern is Frilloechinorhynchus meyeri (Gupta & Naqvi, 1986) (see Bhattacharya 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The shape of the body, size of the proboscis and shape of the uterus of the new species are similar to those of Brasacanthus sphoeroides Thatcher, 2001, an echinorhynchid parasite of Sphoeroides greeleyi, a marine tetraodontid fish from Brazil. However, B. sphoeroides (# 2,460-3,530 9 1,090-1,700; 3,650-6,080 9 1,540-3,120 lm) is larger than the new species (# 1,966-3,135 9 1,092-1,491; $ 3,230-3,800 9 1,615-1,795 lm).…”
Section: Discussionmentioning
confidence: 63%
“…It also differs from other species by having two conspicuous longitudinal areas devoid of hooks, one to either side of the proboscis. It also has a large, robust, cylindrical uterus (''uterine egg reservoir'' sensu Thatcher, 2001), that clearly distinguishes it from all previously described species. Amin (1984Amin ( , 1985aAmin ( , 1986 and Amin & Huffman (1984) recognised three species of Acanthocephalus in North American freshwater fishes and suggested that they can be arranged into two presumably natural groups, primarily by size: the southern species A. alabamensis Amin & Williams, 1983and A. tahlequahensis Oetinger & Buckner, 1976are smaller than A. dirus (Van Cleave, 1931) Van Cleave & Townsend, 1936, which is included in a group of larger species (Amin, 1984) that are more widely distributed in eastern North America.…”
Section: Discussionmentioning
confidence: 91%
“…Sphoeroides, há registros de diferentes táxons em várias partes do mundo, incluindo o Brasil(MARTÍNEZ-AQUINO et al, 2020;FAJER-ÁVILA et al, 2011;ÁLVAREZ-BORREGO e FÁJER-ÁVILA, 2006;DYKOVÁ et al, 2002;THATCHER, 2001;VIDAL-MARTÍNEZ e MENDOZA-FRANCO, 2008).Sphoeroides spengleri tem importância ornamental (FROESE e PAULY, 2019), mas 51,8% dos participantes em ambas as comunidades disseram que o peixe é consumido. Os registros científicos de parasitos nestes três táxons de peixes endossam o conhecimento tradicional local.…”
unclassified